The Effect of Academic Supervision and Leadership Effectiveness on Teacher’s Performance - Martini, Martini; Arafat, Yasir; Rahman, Andi (Yayasan Sembilan Pemuda Indonesia, 2024)
This study was conducted to analyze and describe 1) The influence of academic supervision on teacher performance 2) the effect of leadership effectiveness on teacher performance 3) the influence of academic supervision and leadership effectiveness on teacher performance. The method used in this study refers to quantitative description. This research was conducted at SDN Koba and Lubuk Besar sub-districts with a sample of 82 people. Data collection techniques are carried out through questionnaires, observation, and documentation. Validity tests are conducted through expert and construct validation tests, and instruments are declared valid. Data analysis is carried out through prerequisite tests, namely normality, linearity, multicolonicity, and heteroscedasticity. After prerequisite testing, the analysis continues with regression tests. The results obtained stated that partially: 1) academic supervision affects teacher performance with a significant influence, namely 67%, 2) leadership effectiveness also contributes 51%. Simultaneous testing states that academic supervision and leadership effectiveness contribute significantly to teacher performance, which is 71% and the remaining 29% is influenced by other factors, therefore hypotheses regarding the influence of the two independent variables on the dependent variable can be stated.